Thinking about nuclear weapons principles, problems, prospects - Quinlan, Michael, 1930-2009. (Oxford : Oxford University Press, 2009)
Written by a distinguished policy practitioner in the field of nuclear weapons, this book reflects an exceptional depth of experience in shaping both national and NATO policy. It discusses the significance of the revolution brought about by nuclear weapons, and then considers the problems, costs, and risks which they entail.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nuclear weapons; Nuclear arms control